Dysphagia progression-free survival in patients with locally advanced and metastatic oesophageal cancer receiving palliative radiation therapy - Bhim, Nazreen (Division of Radiation Oncology, 2021)
Purpose: In patients with advanced oesophageal carcinoma palliation of dysphagia is important to maintaining a reasonable quality of life. The primary aim of this study was to determine the dysphagia progression-free survival (DPFS) in patients with advanced oesophageal carcinoma treated with palliative radiotherapy (RT). Methods: The medical records of all patients with oesophageal carcinoma presenting to Groote Schuur Hospital, Cape Town between January 2015-December 2016 were reviewed and patients who were not candidates for curative treatment and received palliative RT were selected. For these patients, the dysphagia score (DS) was recorded prior to RT, 6 weeks after RT and at each follow-up visit. The DPFS was calculated as the time from completion of RT to worsening in DS by ≥1 point or until death. Other outcomes measured were objective change in DS and survival post RT. Results: The study population comprised 84 patients. Squamous cell cancer was the primary histological subtype (93%). The median duration of DPFS after RT was 73 days, with approximately two-thirds of patients remaining able to swallow at least liquids and soft diet until death. The difference in median duration of DPFS was not statistically significant in stented versus non-stented patients (54 days vs 83 days; p =0.224). The mean change in DS was 0.45 ± 0.89 points following RT and the post RT survival was significantly shorter in patients with stent insertion (81 days vs 123 days; p=0.042). Conclusion: Palliative RT can be used successfully to prolong DPFS in patients with locally advanced and metastatic squamous cell cancer of the oesophagus.